2018
DOI: 10.1002/jctb.5871
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Self‐floating Cu/N co‐doped TiO2/diatomite granule composite with enhanced visible‐light‐responsive photoactivity and reusability

Abstract: BACKGROUND The remnants of antibiotics in aquatic environments have emerged as hazardous pollutants. To eliminate these remnants, new methods have been proposed, including photocatalysis. Powdery photocatalysis has been widely studied, yet its several disadvantages such as light‐harvesting and recyclability in suspension systems have remained as bottlenecks for practical applications. A recent report on a floating photocatalyst provided an alternative method to solve the above problems. In the present paper, T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…As shown in Fig. (a), all of their BET isotherms are recognized as type IV based on BDDT classification . The shape of hysteresis loops from 0.5 to 0.9 of relative pressure is identified as H3 according to IUPAC classification, and could be assigned to the slit‐shaped pores, whose sizes are not well‐proportioned .…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Fig. (a), all of their BET isotherms are recognized as type IV based on BDDT classification . The shape of hysteresis loops from 0.5 to 0.9 of relative pressure is identified as H3 according to IUPAC classification, and could be assigned to the slit‐shaped pores, whose sizes are not well‐proportioned .…”
Section: Resultsmentioning
confidence: 99%
“…However, UV light comprises only 4% of the solar light spectrum and thus has inhibited practical applications . Thus, the development of visible‐light‐active photocatalysts is increasingly required for the elimination of OTC in aquatic environments …”
Section: Introductionmentioning
confidence: 99%
“…[21] The strong adsorption capacity of diatomite attracted more target pollutants, enriched them around the photocatalytic reaction sites, provided a larger contact area, and thus improved the decomposition efficiency. [22] Ren's study showed that the chemical binding of Bi 2 O 3 and diatomite improved the formation and thermal stability of phase like, displaying better visible light catalytic activity than Bi 2 O 3 . [23] As far as we know, there are few reports on the photocatalytic oxidation of CIP with LaFeO 3 /Diatomite composite.…”
Section: Introductionmentioning
confidence: 99%